Infective Endocarditis in a Neonate - Dhungana, Sangita Puree; Shrestha, Sabina; Shrestha, Sujit Kumar (Journal of Nepal Paediatric Society, 2018)
Bacterial endocarditis in neonates is a rare. Generally neonates who develop endocarditis have required the invasive intensive care monitoring necessary for the support and treatment of a high-risk nursery population. Neonatal Infective endocarditis is usually reported as a fatal disease. With early diagnosis and treatment we can change prognosis to better side.